Relationship of Socioeconomic Status, Depression and Disease Activity in Patients with Systemic Lupus Erythematosus - Asif Islam, Samara Siddique, Tooba Fatima, Yasir Imran, Tazeen Nazar, Summaya Shabbir, Zainab Younus (Pakistan Journal of Medical & Health Sciences, 2022)
Systemic lupus erythematosus has different presentations and the outcome of this illness is variable. It is associated with significant psychological distress and the outcome of this disease has been shown to be influenced by socioeconomic factors. Objective: To determine the association between socioeconomic status, depression and disease activity in patients with systemic lupus erythematosus. Methodology: It was a cross sectional study carried out at department of Rheumatology, Mayo Hospital, Lahore. 150 patients with systemic lupus erythematosus who fulfilled the inclusion criteria were enrolled. Demographic detail, clinical history and examination findings were noted down. Socioeconomic status was assessed by history, depression was assessed by Beck Depression Inventory and disease activity was assessed by SLEDAI-2K and findings were noted down and was subjected to statistical analysis. Results: The mean age of the patients was 29.12±7.44, mean BDI score was 19.2±10.7 and mean SLEDAI-2K score was 9.94±4.91. There were 33.7% males and 66.3% females. Depression was present in 32% of the patients. Depression was more common in patients with higher scores of disease activity. This association between depression and its severity and the disease activity was found to be statistically significant as indicated by a p value of 0.04. The scores of disease activity were found to be higher in patients who were of middle socioeconomic status and low socioeconomic status i.e. in 48% and 34% respectively and the association was statistically significant (p-value 0.000). Conclusion: Depression, socioeconomic status and disease activity are significantly associated with each other in patients with systemic lupus erythematosus and must be screened in every patient. Keywords: Systemic Lupus Erythematosus, Depression, Socioeconomic status, disease activity